Platinum(II)-Catalyzed Allylation of CO and CN Bonds under Hydrogenation Conditions - Hong, Jong-Tai; Wang, Xi; Kim, Ji-Hwan; Kim, Kyunghee; Yun, Hoseop; Jang, Hye-Young (Advanced synthesis & catalysis, 2010)
The nucleophilic addition of allylplatinum to a range of electrophiles including carbonyls, oximes, and hydrazones was examined. Platinum(II) catalysts and allene substrates were subject to hydrogenation conditions to generate nucleophilic allylplatinum complexes without using a stoichiometric amount of toxic and sensitive organometallic reagents. The allylplatinum intermediates reacted with CO and CN bonds to produce the corresponding homoallylic alcohol and amine derivatives in good yield. The Pt‐catalyzed allylation of CN bonds is the first example performed under hydrogenation conditions. A reaction mechanism initiated with the hydrometalation of allenes by PtH species is proposed based on deuterium labeling studies.